Editorial: Perspectives on history and moral encounters - Niklas Ammert; Heather Sharp; Silvia Edling; Jan Löfström (Historical Encounters: A Journal of Historical Consciousness, Historical Cultures, and History Education, 2022)
We are at a time in world political history that seems to be on a precipice. Over the past decade, it is difficult to ignore the global growth in popularity for autocratic governments, also in some countries which for decades were either strong democracies or moving towards stable democratic governance. The current Russian attack on Ukraine brings into stark focus the political instability many citizens are facing—historical problems are causing, or used as a pretext for, current conflicts. History educators across many sectors—primary, secondary, university, and in public spaces such as museums and galleries – are curious about how these and other current events and issues can and should be approached. The events raise anew the questions of whether and how we can learn from the past, what we value as good and bad in the past, and how these insights might affect our present and future judgements. In relation to this it becomes vital to ponder how educators and members of the public can communicate the situation in Ukraine and similar events to others, while avoiding the bias that presentism can bring.